Aplikasi Quizizz Sebagai Metode Penilaian Tengah Semester di SD Negeri 01 Sinunukan Mandailing Natal - Torang Siregar (Jurnal Intelek Insan Cendikia, 2024)
Abstract This research thoroughly discusses the mid-semester assessment application based on information and communication technology which is implemented at the Lenterahati Islamic boarding school elementary school, namely the Quizzizz application. The aim of this research is to find out what things are implemented in the Quizziz application and what are the benefits of the Quizziz application. The research method used is a qualitative approach using descriptive studies. The sample in this research were teachers in grades 4, 5 and 6. Data collection was obtained from interviews, observation and documentation. The results of the research show that the application of Quizziz at SD Negeri 01 Sinunukan Kabupaten Mandailing Natal has been implemented for 2 semesters or 1 year and is used by grades 4, 5 and 6. This Quizziz application is a very useful application to lighten the workload of educators (teachers) and for students This quizziz application is very useful and fun in answering and working on quiz questions given by the teacher. In conclusion, the application of information and communication technology in the world of education is very important and mandatory so that good educational qualities can be implemented in accordance with the initial objectives in accordance with the benefits of providing education.